Pengaruh Electronic Word of Mouth dan Potongan Harga terhadap Pembelian Impulsif Suatu Produk Skincare - Triana Ariska Wulandari; Muhamad Ikhsanul Insan; Ajat Sudrajat (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
One of the business fields in the field of secondary/tertiary needs that is growing quite rapidly in Indonesia and the city of Karawang, to be precise, is the business in cosmetics. One of the cosmetic fields that are experiencing improvement is skincare. One of the marketing techniques that companies use to attract consumers is Electronic Word Of Mouth or eWOM. In addition, the factor of price discounts can also greatly influence the purchase decision of a product by potential customers and correlates with eWOM, as in e-commerce in Indonesia which always provides discount programs on specific dates. The purpose of this research is to determine whether there is a positive effect of eWOM and Discount on impulsive purchase of skincare products. The method used in this research is the quantitative research method. The data analysis process used the IBM SPSS 21 Software, which processed the data using primary data sources and a questionnaire as the instrument. The interpretation is that there is a positive influence given by two variables independent, namely Electronic Word of Mouth and Discount, on the impulsive buying process of mediheal skincare sheet masks partially and simultaneously.